2013
DOI: 10.5812/archneurosci.11766
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Use of Complementary and Alternative Medicine Among Patients With Epilepsy

Abstract: Background: Complementary and alternative medicine is considered and used by many people with epilepsy to treat seizures, despite the lack of enough scientific proof for its efficacy. Objectives: The aim of the current study was to assess the extent to which patients with epilepsy use complementary and alternative medicine (CAM), and to assess the perceptions of CAM among these patients. Patients and Methods: In this study patients with epilepsy were recruited at two epilepsy centers in Iran (Shiraz and Tehran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…Among 16 papers identified, only eight papers reported the reasons for CAM use. The most commonly reported factors included fear of AED-related side effects (n=4) 31 , 33 – 36 , 40 and poor seizure control (n=3). 28 , 39 , 40 Two studies reported the influence of family members as the reason for CAM usage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 16 papers identified, only eight papers reported the reasons for CAM use. The most commonly reported factors included fear of AED-related side effects (n=4) 31 , 33 – 36 , 40 and poor seizure control (n=3). 28 , 39 , 40 Two studies reported the influence of family members as the reason for CAM usage.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies did not report response rates. 28 , 31 , 33 , 39 , 40 , 46 , 47 , 56 , 58 The manner in which par ticipants were recruited and the sample size was determined were not clearly reported in seven studies. 28 , 29 , 31 , 40 , 46 , 54 Types of CAM used were not explained in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…A self-administered questionnaire was used in this survey. e questionnaire was designed after extensive literature review [16][17][18][19][20][21][22][23][24][25][26][27][28]. e questionnaire was validated by performing face validity from expert biostatisticians and health professionals.…”
Section: Development Of the Questionnairementioning
confidence: 99%
“…Complementary and alternative medicine (CAM) is used by patients with various diseases, including epilepsy [ 3 6 ]. It has been reported that patients with epilepsy often choose herbal medicine among CAM therapies [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%